2006
DOI: 10.1136/tc.2006.016246
|View full text |Cite
|
Sign up to set email alerts
|

Health consequences of reduced daily cigarette consumption

Abstract: Objective: To determine the risk of dying from specified smoking-related diseases and from any cause in heavy smoking men and women (>15 cigarettes/day), who reduced their daily cigarette consumption by .50%. Design: A prospective cohort study. Setting: Three counties in Norway. Participants: 24 959 men and 26 251 women, aged 20-49 years, screened for risk factors of cardiova-?scular disease in the mid-1970s, screened again after 3-13 years, and followed up throughout 2003. Outcomes: Absolute mortality and rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
92
2
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(101 citation statements)
references
References 8 publications
0
92
2
7
Order By: Relevance
“…The use of pharmacologic treatments as partial substitutes to reduce tobacco consumption and therefore morbidity or mortality (harm reduction) has been proposed, but this approach is still not validated. 36 Two approaches that have been proven efficacious for smoking cessation are pharmacotherapy and nonpharmacologic interventions.…”
Section: Management Of Tobacco Use and Dependencementioning
confidence: 99%
“…The use of pharmacologic treatments as partial substitutes to reduce tobacco consumption and therefore morbidity or mortality (harm reduction) has been proposed, but this approach is still not validated. 36 Two approaches that have been proven efficacious for smoking cessation are pharmacotherapy and nonpharmacologic interventions.…”
Section: Management Of Tobacco Use and Dependencementioning
confidence: 99%
“…15 Health risks from light and intermittent smoking are comparable to heavier smoking patterns, 16 the relationship between smoking intensity and cardiovascular disease is notably nonlinear, 17,18 and reducing smoking intensity without abstinence has not been found to improve survival. 19,20 Understanding views that may lead to these smoking patterns is critical. The perceived harm of different tobacco forms correlates with their use.…”
mentioning
confidence: 99%
“…A large Norwegian cohort study followed, until December 2003, smokers who reduced their smoking by 50% or greater (348 males, 127 females; mean number of cigarettes was about 9-10 per day after reduction) between the first screening in the mid-1970s and the second screening 3-13 years later. Reducers experienced a similar relative risk of dying from any cause, cardiovascular disease, ischemic heart disease, and smoking-related cancers and a nonsignificant decrease in lung cancer compared with heavy smokers (17-19 cigarettes/day; Tverdal & Bjartveit, 2006). In a comprehensive literature review on this topic, Hughes & Carpenter (2006) concluded that decreases in risks for smoking-related disease and mortality with smoking reduction have not been tested adequately because of measurement limitations in the present studies (e.g., reliance on selfreport, no information on duration of reduction).…”
Section: Methods and Mechanismsmentioning
confidence: 99%